GREMPA: A useful initiative for cooperation in almond research - Socias i Company R. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The first GREMPA Colloquium was held at the Mediterranean Agronomic Institute of Zaragoza in February 1974, but was preceded by several initiatives mainly driven by Dr. Jacques Souty, Director of the Station of the Grande Ferrade of INRA in Bordeaux. Many of these previous actions are not well known, but were essential for the launching of such a useful group. In this review I have attempted to follow up these initiatives,as well as the first aims proposed for the success of GREMPA. Many of these objectives have been achieved, but the initial spirit of dialogue and open discussion has changed towards a more formal, congress style meeting. Additionally, some conflictive moments of the history of GREMPA are recalled and homage is paid to the three great researchers who invested all their energy in this endeavour: A.J. Felipe, C. Grasselly and F. Monastra, whose enthusiasm and spirit we have not managed to maintain.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)